Partitioning variation in vegetation communities around Lajaneh Piosphere, Iran. Issue 1 (2nd January 2021) - Shahriary, Eahsan; Langford, Richard P.; Gill, Thomas E.; Hussein, Musa; Hargrove, William L.; Golding, Peter
Abstract: The concentration of grazing around artificial and natural watering points in an arid region produces a system known as a piosphere. This study focused on the Lajaneh Piosphere, located in a dry Zygophyllum eurypterum shrubland in north-east Iran. Vegetation and soil were sampled in Lajaneh Piosphere, to discern what amount of variation in plant species composition along a piosphere can be explained by environmental variables in addition to distance from the watering point. Elevation and geographical data were recorded along three transects extending across widely varied terrain up to 5 km from the piosphere. Redundancy Analysis (RDA) and partial Redundancy Analysis (pRDA) were used to evaluate the vegetation distribution as related to soil phosphorus (P), soil potassium (K), soil nitrogen (N), slope, aspect, elevation, and distance from water. Cover of palatable plant species increased with distance from the artificial watering point. Although the redundancy analysis resulted in much unexplained variation, we found the role of soil fertility factors and distance from water most important to plant species composition; soil nitrogen (N) (7.26%), soil phosphorus (P) (5.13%), soil potassium (K) (4.47%), and distance from water (1.77%) explained variations in vegetation community more than elevation (0.91%), aspect (0.42%) and slope (0.05%). Although the transects extended across a varied terrain through a gorge into an adjacent basin and onto a plateau ∼100 m above and below the watering point on the basin floor, distance from the piosphere still was more important in explaining plant species variance than topographic factors. In general, the grazing pressure decreased with distance from water and related with high concentration of soil nutrients. Understanding the magnitudes and orders of effects of different environmental variables on piospheres such as Lajaneh provides important understanding of environmental stresses in arid landscapes. Piospheres deserve further investigation to provide a basis for studying sustainable land management in arid and semi-arid regions.